Hak Anak Angkat Dalam Hukum Keluarga Islam di Indonesia - Syaf, Alzekrillah; Akbarizan, Akbarizan (MUI Kota Pekanbaru, 2023)
This research states that in Islamic law adopting a child is a good act, which helps adopted children get a proper education. The right to a proper education for adopted children is one of the main goals of adoption, this welfare is one of the rights that must be provided by adoptive parents. In general, implementing the above rights of children is an obligation and joint responsibility of the government and society. The phenomenon that occurs in Indonesia is that the educational rights of adopted children have shifted to utilization, due to several factors, one of which is economic. The aim of this research is to strengthen previous research, and examine further the shift in the educational rights of adopted children and look at the factors that result in non-fulfillment of adopted children's rights in Indonesia. This research uses an approachsociological normative with the nature of the researchanalytical descriptive. The results of this research found several factors that resulted in a shift, even not being given the rights of adopted children, such as: f In fact, in Islam, adopting a child is a good act but over time it becomes exploitative.